Antimicrobial active packaging based on PVA/Starch films incorporating basil leaf extracts. (2023) - Varghese, Sandhya Alice; Pulikkalparambil, Harikrishnan; Rangappa, Sanjay Mavinkere; Parameswaranpillai, Jyotishkumar; Siengchin, Suchart
Abstract: The current work focuses on the development of PVA/starch films incorporated basil leaf water extract as an antimicrobial agent. The mechanical properties, contact angle studies, antimicrobial, and packaging studies were conducted. All films after the addition of basil leaf extracts maintained the tensile strengths and were comparable to neat PVA/starch films. The antimicrobial tests showed excellent inhibition against the two tested pathogens- S. aureus and E. coli . The packaging films developed were tested for the storage of fresh green chillies for 7 days, and it showed that the chillies wrapped in films containing basil extract resulted in better maintenance of freshness compared to unpacked ones. The results of the current work suggest that these films developed can be successfully used for the packaging of delicate vegetables and fruits.